Natural Compound ZINC12899676 Reduces Porcine Epidemic Diarrhea Virus Replication by Inhibiting the Viral NTPase Activity - Wang, Pengcheng; Wang, Xianwei; Liu, Xing; Sun, Meng; Liang, Xiao; Bai, Juan; Jiang, Ping (Frontiers in Pharmacology, 2022)
Porcine epidemic diarrhea virus (PEDV) is an alphacoronavirus (α-CoV) that causes high mortality in suckling piglets, leading to severe economic losses worldwide. No effective vaccine or commercial anti-viral drug is readily available. Several replicative enzymes are responsible for coronavirus replication. In this study, the potential candidates targeting replicative enzymes (PLP2, 3CLpro, RdRp, NTPase and NendoU) were screened from 187,119 compounds in ZINC natural products library. And seven compounds had high binding potential to NTPase and drug-like property. Among them, ZINC12899676 was identified to significantly inhibit the NTPase activity of PEDV, by targeting its active pocket and causing its conformational change. And ZINC12899676 significantly inhibited PEDV replication in IPEC-J2 cells. It first demonstrated that ZINC12899676 inhibits PEDV replication by targeting NTPase and then NTPase may serve as a novel target for anti-PEDV.